POTENSI EKSTRAK BUNGA ROSELLA (Hibiscus sabdariffa L.) SEBAGAI PEWARNA DAN PENGAWET ALAMI PADA JELLY JAJANAN ANAK - Handarini, Kejora (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
Jelly is a highly preferred snack of children, but was reported that jelly products sometimes containing a non food grade dyes and harmful preservatives, whict is’s used for textile processed usually. Rosella flower extracts was containing antibacterial activity such as alkaloid, saponin tanin, and high anthocyanin that could be nature dye. The purpose of this study is to determine how the optimal concentration of roselle flowers extracts can be applied to jelly as a natural dye and preservatives. The methods were: a. extraction of rosella flower. b. application of an extract rosella flower onto the jelly product (the treatments are A0: 0 %A1 : 0.5 % , A2 : 1 % , A3 : 1.5 %) and then storage at refrigeration temperature for 0, 5, and 10 days .Parameters measured were the Total Plate Count (TPC), total mold-yeasts, total coliforms, and product color observations. The results showed for the storaging in 0 to 5 days, roselle jelly with various concentrations have indigenous microbial contaminants (the TPC, mold- yeasts and coliforms) is smaller than the control ( A0: 0% ). While the 10-day storaged, the TPC values , molds - yeasts and coliforms in jelly with roselle extracted was lower than controls, but for all treatments had an exceeding value than the microbiological standards. The results of colour with organoleptic test showed for 0 to 5 days of storage refrigerator, showed that roselle jelly A3 ( 1.5 % ) has the best value compared to other treatments, the value of a little love to love ( and its value is higher than controls). On the 10th day of storaged, for the treatment of roselle jelly A1, and A2 has a value of color under control, while the A3 is equal to the control. Based on the microbiological and organoleptic tests, the best roselle jelly is A3 sample and 5 days storaged in the refrigerator.Kata Kunci: Rosella, pengawet alami, pewarna alami, jelly